UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT MEMBACA MELALUI KEGIATAN LITERASI SISWA KELAS X C1 MIPA DI SMAN 5 MALANG - Hikmatul Maula; Mohammad Afifulloh; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This research begins from the reality that occurred in Indonesia which has many problems in the field of education, especially in the field of religion. The researcher conducted the research on the tenth-grade students at MIPA class of SMAN 5 Malang because there are some various problems and advantages in this school that want to be explored more deeply by the researcher. In this research, the researcher wants to find out about how the conditions of students' interest in the reading activity. The researcher also wants to know about the efforts and obstacles encountered by teachers during increasing students' interest in reading activity through literacy. Hence, the researcher conducted this research by using descriptive qualitative design. The instruments used in this research were observation, interview, and documentation. The researcher analyzes the data through data reduction, data presentation, and data conclusions. The results of this study showed that the students' interest in the reading activity categorized in good enough. The teachers can be more increased students' interest in the reading activity trough students' literacy activity. The implementation of IMTAQ activities held by PAI teachers every morning before starting the learning activity in the school was very beneficial for the students. This might require cooperation between related parties so this activity can be more maximized and effective for the future.